Broad and robust T cell immunity compensates the population immune barrier against antibody-escaping Omicron variants - Guo, Yuanyuan; Guo, Peipei; Tian, Jinmin; Tuluhongtayi, Yeerzati; Song, Rui; Gao, George F.; Zhao, Xin; Liu, Jun (Frontiers in Immunology, 2026)
BackgroundContinuous SARS-CoV-2 Omicron emergence poses challenges to immune protection from the previous infection/vaccination in the population. While neutralizing antibodies serve as a key immune protection indicator, their cross-protective effect against novel variants remains limited. However, T cell immunity may confer more durable and broad-spectrum protection.MethodsWe evaluated immune dynamics in four Chinese cohorts comprising BF.7/BA.5.2, XBB, and JN.1 convalescents, plus tetravalent recombinant protein vaccine recipients. Neutralizing antibodies were assessed against nine variants spanning the emerging evolutionary spectrum. T cell responses were characterized using variant-specific peptide pools. Antigenic relationships were analyzed through multidimensional scaling-based cartography.ResultsBF.7/BA.5.2 convalescents exhibited progressive antibody evasion, with fold-changes against heterologous variants increasing from 4–12-fold initially to > 20-fold at 6 months. XBB convalescents maintained stable short-term responses, while JN.1 convalescents showed superior cross-reactivity against descendant lineages. BA.3.2 demonstrated maximal immune evasion across all groups, occupying the most distant antigenic position. In contrast, T cell immunity exhibited remarkable stability and cross-reactivity, maintaining elevated levels at 6 months with balanced responses against all tested variants. The tetravalent vaccine induced broad-spectrum T cell responses comparable to natural infection, and elicited cross-neutralizing antibody responses against different Omicron variants.DiscussionOur study reveals SARS-CoV-2 variant-specific antibody escape compensated by stable cross-reactive T cell responses. In the context of continued viral evolution, stimulating robust T cell immune responses may be critical to achieve a high population immune barrier against future coronaviruses/variants. These findings emphasize the necessity of comprehensive immune evaluation integrating both humoral and cellular components and provide scientific foundations for optimizing vaccine strategies and immune surveillance systems to address emerging viruses and their variants.